Photooxidation triggered ultralong afterglow in carbon nanodots - Zheng, Guang-Song; Shen, Cheng-Long; Niu, Chun-Yao; Lou, Qing; Jiang, Tian-Ci; Li, Peng-Fei; Shi, Xiao-Jing; Song, Run-Wei; Deng, Yuan; Lv, Chao-Fan; Liu, Kai-Kai; Zang, Jin-Hao; et al. (Nature communications, 2024)
It remains a challenge to obtain biocompatible afterglow materials with long emission wavelengths, durable lifetimes, and good water solubility. Herein we develop a photooxidation strategy to construct near-infrared afterglow carbon nanodots with an extra-long lifetime of up to 5.9 h, comparable to that of the well-known rare-earth or organic long-persistent luminescent materials. Intriguingly, size-dependent afterglow lifetime evolution from 3.4 to 5.9 h has been observed from the carbon nanodots systems in aqueous solution. With structural/ultrafast dynamics analysis and density functional theory simulations, we reveal that the persistent luminescence in carbon nanodots is activated by a photooxidation-induced dioxetane intermediate, which can slowly release and convert energy into luminous emission via the steric hindrance effect of nanoparticles. With the persistent near-infrared luminescence, tissue penetration depth of 20 mm can be achieved. Thanks to the high signal-to-background ratio, biological safety and cancer-specific targeting ability of carbon nanodots, ultralong-afterglow guided surgery has been successfully performed on mice model to remove tumor tissues accurately, demonstrating potential clinical applications. These results may facilitate the development of long-lasting luminescent materials for precision tumor resection. Biocompatible afterglow materials have potential in imaging applications, but are challenging to prepare. Here the authors report the development of carbon nanodots with near-infrared afterglow, and demonstrate their use in imaging for tumour resection.